Controlled and healthy breeding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Avoiding in-breeding, timing new births, choosing goats for mating, feeds for breeding animals, and care of kids.